"What if It's not Just an Item of Clothing?" – A Narrative Review and Synthesis of the White Coat in the Context of Aged Care. Issue 1 (23rd February 2022) - Crutzen, Coline; Adam, Stéphane
Although increasingly disputed, the white coat uniform is ubiquitous in geriatric care, which may reflect a phenomenon called medicalisation of ageing. This narrative review is the first attempt at integrating several theoretical approaches, such as the "white coat effect" and "enclothed cognition", in order to gain a comprehensive understanding of the use of this clothing item. Based on extensive empirical evidence, we will examine the consequences of wearing a uniform, not only on patients (in this case, older patients) and healthcare professionals, but also on their relationship. The white coat has powerful symbolic functions for healthcare professionals and is still preferred by older adults. However, the negative repercussions of wearing a uniform require us to question its use, particularly in environments where older persons live, such as nursing homes.